Penentuan Penerimaan Usulan Penelitian Internal Dosen Menggunakan Metode Profile Matching - Vivi Sahfitri (ISB Atma Luhur, 2020)
A Lecturer as an educator in Higher Education System has an obligation to fulfill the Tri Dharma University which consists of Education, Research and Community Service. A research, which is a part of the lecturer responsibility, shall be conducted in various activities with the cost coming from a wide range of sources. Bina Darma University through the Research and Community Service Institute has an agenda to administer Internal Research Grants which aim to facilitate and motivate Lecturers in the research activities. The assessment of Research proposal is carried out by a reviewer appointed directly by the institution. The reviewer has a full right to determine whether the proposal would be funded or not. The reviewer's full right may affect the objectivity of assessment by the Reviewer which eventually would influence the final decision. Thus, this research aims to design a system for determining the acceptance of Internal Research proposals, that is by using the implementation of Profile Matching Method. The final result of the study shows that the final value of the research proposal which will get the first rank is the value of the ID PROP007 with the final value 4.55. Meanwhile, the lowest end value is 3.1 obtained by ID PROP004. The assessments criteria contained in the research proposal include abstract, introduction, literature review, research methodology, budget conformance and research schedule.